Systematic review of the incidence and risk factors for cerebral vasculopathy and stroke after cranial proton and photon radiation for childhood brain tumors. Issue 1 (28th September 2020) - Bavle, Abhishek; Srinivasan, Anand; Choudhry, Farooq; Anderson, Michael; Confer, Michael; Simpson, Hilarie; Gavula, Theresa; Thompson, J Spencer; Clifton, Shari; Gross, Naina L; McNall-Knapp, Rene
Abstract: Background: The aim of our study is to determine the incidence, timing, and risk factors for cerebral vasculopathy after cranial proton and photon radiation for pediatric brain tumors. Methods: We performed a single-institution retrospective review of a cohort of children treated with proton radiation for brain tumors. MRA and/or MRI were reviewed for evidence of cerebral vascular stenosis and infarcts. Twenty-one similar studies (17 photon, 4 proton) were identified by systematic literature review. Results: For 81 patients with median follow-up of 3 years, the rates of overall and severe vasculopathy were 9.9% and 6.2% respectively, occurring a median of 2 years post radiation. Dose to optic chiasm greater than 45 Gy and suprasellar location were significant risk factors. Results were consistent with 4 prior proton studies (752 patients) that reported incidence of 5% to 6.7%, 1.5 to 3 years post radiation. With significantly longer follow-up (3.7-19 years), 9 studies (1108 patients) with traditional photon radiation reported a higher rate (6.3%-20%) and longer time to vasculopathy (2-28 years). Significant risk factors were neurofibromatosis type 1 (NF-1; rate 7.6%-60%) and suprasellar tumors (9%-20%). In 10 studies with photon radiation (1708 patients), the stroke rate was 2% to 18.8% (2.3-24 years post radiation). Conclusions: Childhood brain tumor survivors need screening for vasculopathy after cranial radiation, especially with higher dose to optic chiasm, NF-1, and suprasellar tumors. Prospective studies are needed to identify risk groups, and ideal modality and timing, for screening of this toxicity.